2019
DOI: 10.1590/0074-02760190232
|View full text |Cite
|
Sign up to set email alerts
|

Acinetobacter baumannii infections in Amazon Region driven by extensively drug resistant international clones, 2016-2018

Abstract: BACKGROUND Acinetobacter baumannii is a leading cause of nosocomial infections. This species is characterised by the presence of pandemic lineages (International Clones) that present a broad antimicrobial resistance profile.OBJECTIVE To perform the molecular epidemiology of carbapenem-resistant A. baumannii from a clinical setting in the Amazon Basin, and to characterise their antimicrobial resistance determinants.METHODS The genetic relationship of carbapenem-resistant A. baumannii were assessed by pulsed-fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 32 publications
0
10
1
2
Order By: Relevance
“…Tn2008 is similar to Tn2006 but lacks the second copy of ISAba1 and the bla OXA-23 gene is associated with one copy of ISAba4 (which differs from ISAba1) in Tn2007 [132]. While OXA-23-like enzymes are commonly associated with hospital outbreaks, and pandemic clones producing these enzymes are identified [260,261], other families like OXA-58, OXA-143, and OXA-235 are identified on a more limited or sporadic basis, as explained above in Section 5. bla OXA-23 has been detected in A. baumannii from companion animals at veterinary clinics in Germany, on plasmids with Tn2008 [262]. Therefore, resistance determinants and clonal lineages of A. baumannii strains globally emerging in humans require close molecular surveillance to monitor this interspecies spread and mitigate its effect on both human and non-human hosts.…”
Section: Acinetobactermentioning
confidence: 99%
“…Tn2008 is similar to Tn2006 but lacks the second copy of ISAba1 and the bla OXA-23 gene is associated with one copy of ISAba4 (which differs from ISAba1) in Tn2007 [132]. While OXA-23-like enzymes are commonly associated with hospital outbreaks, and pandemic clones producing these enzymes are identified [260,261], other families like OXA-58, OXA-143, and OXA-235 are identified on a more limited or sporadic basis, as explained above in Section 5. bla OXA-23 has been detected in A. baumannii from companion animals at veterinary clinics in Germany, on plasmids with Tn2008 [262]. Therefore, resistance determinants and clonal lineages of A. baumannii strains globally emerging in humans require close molecular surveillance to monitor this interspecies spread and mitigate its effect on both human and non-human hosts.…”
Section: Acinetobactermentioning
confidence: 99%
“… 15 The MLST revealed that all of them belonged to ST79 PAS / ST758 OXF , which corresponds to the high-risk pandemic International Clone V (IC-5), while the 456MDp strain belonged to ST1079 PAS already identified in China in 2015 (MLST metadata). The IC-5 is prevalent in clinical settings spread in Brazil and South America, 21 however, the pigment production has never been highlighted as a phenotypic trait of this IC neither in Brazil nor in other continents. Interestingly, this lineage has persisted in HGR for more than one year (19 months), which could be resulted from an increased adaptive fitness.…”
Section: Resultsmentioning
confidence: 99%
“…(15) All 12 strains belonged to ST79 PAS /ST758 OXF , which corresponds to the high-risk pandemic International Clone V (IC-5), while the 456MDp strain belonged to ST1079 PAS /ST1483 OXF already identified in China in 2015 (MLST metadata). The IC-5 is prevalent in clinical settings spread in Brazil and South America, (21) however, the pigment production has never been highlighted as a phenotypic trait of this IC neither in Brazil nor in other continents. Interestingly, this lineage has persisted in HGR for more than one year (19 months), which could be resulted from an increased adaptive fitness.…”
Section: Resultsmentioning
confidence: 99%